Cardiothoracic Surgery in the Elderly Evidence-Based Practice - Katlic, Mark R.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Cardiothoracic Surgery in the Elderly: Evidence Based Practice is an important and timely book that reflects the thoughtful work of pioneers in geriatric surgery. It encompasses their knowledge related to geriatric surgery, and their reflections and guidance on the rapidly accumulating knowledge related to improving the health and surgical care of seniors. This book provides a scholarly review of the constantly expanding knowledge base about cardiovascular and thoracic surgery in seniors. The book follows a logical sequence covering general aspects of care, cardiac surgery and thoracic surgery. Chapters are focused on common, devastating and often missed complications of surgical care in the seniors. These include delirium, depression, pressure sores, functional losses, incontinence, volume depletion and asymptomatic or atypical complications -myocardial infarction, post-operative diarrhea, urinary track infections and pneumonia. Each is expertly reviewed. Strategies to help the surgeons and the surgical team anticipate, recognize and effectively prevent or manage such problems are discussed and the evidence basis for such strategies is provided. Cardiothoracic Surgery in the Elderly: Evidence Based Practice is particularly timely and the first to review the substantial body of knowledge that has been developed in recent years related to geriatric cardiothoracic surgical problems. It catalogs well the expanding knowledge basis for achieving successful surgical outcomes in the very old. It provides a most useful resources for cardiovascular thoracic surgeons in training and those already in practice.
Invited Commentary -- The Epidemiology and Economics of Cardiothoracic Surgery in the Elderly -- Principles of Geriatric Surgery -- Geriatric Models of Care -- Delirium after Cardiac Surgery -- Cardiac Rehabilitation in the Elderly -- Legal Aspects of Geriatric Surgery -- Ethical Issues in Cardiac Surgery for the Elderly -- Acute Pain Control in Geriatric Patients after Cardiac and Thoracic Surgeries -- Palliative Care in the Elderly -- Cardiopulmonary Trauma in the Elderly -- Imaging Features of the Normal Aging Chest -- Cardiac Imaging in the Elderly -- Invited Commentary -- Biology of Aging -- Hematologic Disorders in the Elderly -- Anticoagulation in the Older Surgical Patient -- Medication Usage in Older Cardiothoracic Surgery Patients -- Wound Healing in the Elderly -- Pulmonary Changes in the Elderly -- Cardiac Changes in the Elderly -- Renal Changes in the Elderly -- Gastrointestinal and Liver Changes in the Elderly -- Neurologic and Cognitive Changes in the Elderly -- Hormonal Changes during and after Cardiac Surgery -- Invited Commentary -- Preoperative Evaluation and Preparation in the Elderly Cardiac Surgery Patient -- Cardiac Anesthesia in the Elderly -- Cardiothoracic Surgery in the Elderly -- Ischemic Coronary Disease -- Surgical Treatment of Aortic Valve Disease in the Elderly -- Surgical Treatment of Mitral Valve Disease in the Elderly -- Surgical Treatment of Thoracic Aortic Disease in the Elderly -- Surgical Treatment of Pericardial Disease in the Elderly -- Pacemakers and Implantable Cardioverter Defibrillators in the Elderly -- Heart Transplant and Mechanical Assistance in the Elderly -- Invited Commentary -- Preoperative Evaluation and Preparation in the Elderly Thoracic Surgery Patient -- Thoracic Anesthesia in the Elderly -- Postoperative and Critical Care in the Elderly Thoracic Surgery Patient -- Adjuvant Therapy for Lung Cancer in the Elderly -- Pulmonary Surgery for Malignant Disease in the Elderly -- Benign Thoracic Disease in the Elderly -- Lung Transplantation in the Elderly -- Esophageal Surgery for Malignant Disease in the Elderly -- Esophageal Surgery for Benign Disease in the Elderly -- Surgery for Mediastinal Disease in the Elderly -- Surgery for Pleural Disease in the Elderly -- Surgery for Chest Wall Disease in the Elderly -- Surgery of the Trachea and Bronchi in the Elderly -- Indices -- Function -- Physiologic -- References.
Keywords: Medicine; Geriatrics; Abdomen -- Surgery; Heart -- Surgery; Surgery; Thoracic surgery; Medicine & Public Health; Cardiac Surgery; Abdominal Surgery; General Surgery; Thoracic Surgery; Geriatrics/Gerontology.